Assessment of Tertiary Education in Nigeria - Jovita Chika Opara (Researchparks Publishing, 2023)
This paper assessed the challenges facing tertiary education in Nigeria with the view of addressing them systematically. To do this, the paper employs the use of content analysis to extract pieces of literature fit that are suitable for the topic. Secondary data were the major data used in the paper and they were collected from both print and online publications. The paper concludes that inadequate funding, infrastructural facilities, shortage of personnel, Integrated Payroll and Personnel Information System (IPPIS), indigenization of Principal Officers, cultism/insecurity, Autonomy, leadership, Brain-drain syndrome and poor motivation are some of the problems that are facing tertiary education in Nigeria. Based on these problems identified, the paper suggested the following: the government should increase the funding of tertiary institutions in Nigeria. There should be a master plan for infrastructural facilities development in all the tertiary institutions in Nigeria. The government should direct all tertiary institution administrators to employ more staff. The federal government should remove the tertiary institutions' staff from Integrated Payroll and Personnel Information System (IPPIS). The government should discourage the indigenization of Principal Officers in public institutions and insist on merit in the appointment of principal officers of tertiary institutions in Nigeria, etc.